Platelet and endothelial activation in catastrophic and quiescent antiphospholipid syndrome - Bontadi, Agnese; Ruffatti, Amelia; Falcinelli, Emanuela; Giannini, Silvia; Marturano, Alessandro; Tonello, Marta; Hoxha, Ariela; Pengo, Vittorio; Punzi, Leonardo; Momi, Stefania; Gresele, Paolo (Thrombosis and Haemostasis, 2013)
Antiphospholipid antibodies (aPL) seem to induce a prothrombotic state by activating endothelium and platelets, but no studies have evaluated systematically the effects of aPL from patients with the antiphospholipid syndrome (APS) in quiescent versus catastrophic phase. Our aims were to evaluate the in vitro effects on platelet activation of anti-β2 glycoprotein I (anti-β2GPI) antibodies isolated from APS patient in either quiescent or catastrophic phase and to investigate ex vivo platelet and endothelial activation in patients with quiescent or catastrophic APS. Anti-β2GPI antibodies were isolated from plasma of a pregnant woman in two different stages of APS (quiescent and catastrophic, respectively). They were co-incubated with washed platelets from healthy controls that were then challenged with TRAP-6 (thrombin receptor activating peptide 6) and the expression of P-selectin (P-sel) on platelets was assessed by flow cytometry. Moreover, plasma samples from six patients with quiescent, four with catastrophic APS and 10 controls were assessed for several markers of platelet and endothelial activation. The results showed that purified anti-β2GPI antibodies co-incubated with platelets enhanced TRAP-6-induced platelet P-sel expression. Notably, anti-β2GPI antibodies isolated during the catastrophic phase enhanced platelet P-sel expression more than antibodies isolated from the same patient in the quiescent stage of disease. Moreover, APS patients had significantly higher plasma levels of soluble (s) Psel, sCD40 ligand, soluble vascular cell adhesion molecule 1 and monocyte chemoattractant protein 1 than control subjects. In addition, sP-sel and von Willebrand factor activity were significantly higher during catastrophic than in quiescent phase.
Keywords: Anti-β2glycoprotein I antibodies; antiphospholipid syndrome; catastrophic antiphospholipid syndrome; endothelial activation; platelet activation